Changes in physical characteristics and performance of elite sailors following introduction of a sport science programme prior to the 1996 olympic games - Legg, S. J.; Mackie, H. W.; Slyfield, D. A. (Applied Human Science, 1999)
The objective of this study was to examine changes in sailors' physical characteristics during three different time periods immediately before the 1996 New Zealand Olympic trials, as a result of a newly introduced sport science programme. Twenty five (19 male and 6 female) Olympic development squad members volunteered as subjects and completed fitness tests at different times between April 1995 and March 1996 after being administered with individualised physical training programmes. Statistically significant improvements were observed in body weight, sum of skinfolds, flexibility (assessed using a sit-reach test), aerobic endurance (assessed using a maximal effort 2500 m rowing test) and strength (assessed as the maximum number of push-ups, pull-ups, and sit-ups that could be completed in 2 minutes) over the three time periods. Thus, physical training was effective in improving many aspects of sailors' fitness, especially early in the sailing season as a result of pre-season training. Physical performance correlated poorly with both light and heavy wind racing performance. The results suggest that individually tailored training programmes will increase sailing specific fitness. However, it is impossible to know what proportions of racing performance can be attributed to physical fitness, skill, talent, and technology, therefore the effect of physical training on racing performance is difficult to determine.